Miskonsepsi Konsep Prasyarat Aljabar Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah - Nurlita Nurlita; Cut Morina Zubainur; Anizar Ahmad; Saiman Saiman (Universitas Syiah Kuala, 2016)
The concept of algebra prerequisites that must be understood by primary school teachers (SD) including: (1) concept of numbers and numerical operations, (2) the ratio/proportion, and (3) the order of operations. The third prerequisite concept also needs to be understood as a candidate in primary students in elementary uru. Lack of understanding of the concept of preconditions can lead to misconceptions in students. The researchers aim to analyze the misconceptions of what happens to students in primary prerequisite to the concept of algebra. The study involved five students in primary UIN Ar-Raniry. Data obtained through diagnostic tests and interviews so analyzed descriptively qualitative. The results showed that students in primary experiencing misconceptions on the concept of algebra prerequisites are: the concept of fractions, prime numbers, integers, mixed operations, and operations on fractions. The implication of the study is the need for efforts to improve understanding of student teachers, especially students in primary through appropriate measures.